Metodología para fortalecer la exposición magistral usando TIC en un curso de programación de computadores en un programa de ingeniería (2016)
In this article we examine the possible changes that occur in computer programming course when we use TIC strategies to capitalize them, all from a classroom implementation and design centered masterly exposition. The methodology used is framed in educational qualitative research with a quantitative component in conjunction with a case study. We use (simultaneous) the word processor Word, PowerPoint slides designer, the Dev-C++ development environment and the browser Google Chrome. The results show that with a simultaneous use of ICT in a course of computer programming, not only masterly exposition is strengthened notoriously but establishes more meaningful learning with more sense, strengthening independent learning and appropriation of knowledge in the long term.